PENINGKATAN MOTIVASI BELAJAR BIOLOGI SISWA MELALUI STRATEGI PEMBELAJARAN INKUIRI PADA ERA NEW NORMAL DI MADRASAH ALIYAH MUHAMMADIYAH 6 KOTANOPAN - Lubis, Fitri Agustina; Rambe, Aslamiyah; Lubis, Mutiara; Mardiyah, Ainun; Sarah, Putri Mei (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2023)
The lack of student motivation to study biology is a challenge for researchers. Research (PTK) through inquiry learning strategies in the new normal period to overcome problems. Research objectives: 1) to increase student motivation through inquiry teaching strategies in the new normal era in class XI Madrasah Aliyah Muhammadiyah 6 Kotanopan. 2) improving student learning outcomes through inquiry teaching strategies in the new normal era of class XI Madrasah Aliyah Muhammadiyah 6 Kotanopan. . Students of class XI MAM 6 totaling 14 students were used as research subjects. This type of research is known as PTK, coined by McTaggart (Arikunto: 2013). The activity procedure consists of two cycles. The stages of an activity begin with activity planning, activity implementation, activity observation, and activity reflection. Increased motivation can be seen from learning data that has been analyzed from students, while information about learning motivation is collected from questionnaires filled out by students who have a percentage value of cycle I, 64% in cycle II, 78% indicating an increase in research results. Increase in cycle I results, 71% in cycle I I to 85% Based on the findings of this study, students of class XI MAM 6 Kotanopan can be more motivated to study biology by applying an inquiry-based learning methodology.